Assessing the micro-level impact of COVID- 19 lockdowns on urban households’ economic well-being - Benjamin Amoah; Anthony Amoah (Discover Cities)
Abstract In this empirical study, we investigated the impact of the COVID- 19 lockdown on the economic well-being of individuals in urban Ghana, using cross-sectional survey data. The outcome variables representing economic well-being are proxied by individuals’ income, savings, and investments in the three quarantined cities of Accra, Kumasi, and Tema. Using ordinary least squares and quantile regression techniques, we provide evidence that relative to non-quarantined cities, individuals in all three cities, on average, spent a higher proportion of their income during the lockdown period. Additionally, we show that Accra residents experienced relatively greater depletion in their savings. Robustness checks confirmed these findings, suggesting that the economic well-being measures in quarantined cities were significantly affected by the lockdown. This study, using micro-level data from a developing economy, demonstrates that the COVID- 19 lockdown had a notable impact on economic well-being measures, such as income and savings, albeit not investment.